A Comprehensive Survey on Deepfake Detection Techniques - Sultan, Duha A.; Ibrahim, Laheeb M. (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Improving machine learning and artificial intelligence makes it possible to swap someone else’s face and voice in a high realism video which made distinguishing the difference between the real and fake videos difficult. Although this technology can be used in many useful fields like advertising, video gaming, and film industry, most of the time it is used for malicious purposes. Therefore, many studies have been done to understand how deepfake works and how to detect these fake videos or images. In this paper, an inclusive study is presented on the existing techniques used for creating and detecting fake materials and analyzing these techniques that are used by several researchers in addition to the great role of artificial intelligence and deep learning on improving them.